Етапи створення й реалізації акме-технології формування математичної культури студентів за напрямом підготовки "Програмна інженерія" - Дубініна, Оксана Миколаївна (Класичний приватний університет, 2014)
У статті з метою створення технологічного фундаменту підготовки студентів у технічних вищих навчальних закладах, об’єктивно затребуваного сучасним ринком праці, наведено етапи розробки акме-технології формування математичної культури майбутніх інженерів з виробництва програмного забезпечення автоматизованих систем управління та електронних пристроїв. Виокремлено специфічні вимоги до пропонованої акме-технології, визначено основні методологічні підходи, що детермінують провідні принципи організації педагогічного процесу в дидактичному просторі програмної інженерії, методи, застосовувані в ході практичної реалізації акме-технології.

In the article with the aim to create a technological foundation of training of students in technical high schools demanded by today’s job market are the stages of acme – technology of formation of mathematical culture of the future engineers from production of automatic control systems and electronic devices. Are pointed out specific requirements for the proposed acme technology, main methodological approaches that define the major principles of organization of educational process in the didactic area of software engineering, dominant methods used in the practical implementation of Acme Technologies. Educational technology of acme-mathematical culture is an integrated system of methods and means with the aim to achieve a high level of professionally designed mathematical culture, to form the intellectual, behavioral and professional status of future specialists. The entire process of step by step development of content of teaching activities of teachers and students, procedural characteristics of acme technology, development of software methods were divided into six stages of development, namely: stage of forecasting, pedagogical design, pedagogical forecasting, construction, testing, completing with implementation phase. Prospects of the proposed acme technology is providing new content of engineering education based on a set of competencies that include fundamental and technical knowledge, ability to analyze and solve problems using an interdisciplinary approach, mastering the techniques of project management, communication and commitment to teamwork.
Stages of implementation and acme-technologies of mathematical culture of the students in the field of "Software engineering"
Keywords: програмно-методичне забезпечення; прогнозування; педагогічне проектування; апробація; командна робота; pedagogical acme technology; stages; mathematical culture; software engineering